ANTI-EUROPEAN DISCOURSE AND NEGATIVE IMAGE OF THE EUROPEAN UNION IN THE SERBIAN MEDIA - Drašković, Brankica; Prodanović, Dragana; Pavkov, Ksenija (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
This paper presents the results of research on the representation of the process and actors of Europeanization in the Serbian media. The analysis included 243 texts sampled from 13 to 19 June 2016 in the online editions of the daily newspapers Danas, Informer, Politika and Blic.The Europeanisation in the paper was not observed just as a technical aspect of the process, it was rather widely perceived as a discursive practice used for explaining, describing and defining social and political activities. To determine the key mechanisms for creating the image of Europeanization and actors of that process, a method of critical discourse analysis is applied. Special attention was paid to the analysis of lexical constructs and metaphors used to describe the process of Europeanization. Since one of the goals of the paper was to determine to what extent the presentation of this process in the media discourse has changed in comparison with previous research from 2012, comparative analysis is used as a complementary method. The results show an increased Euro-skepticism in the media discourse and in the discourse of the actors of the process of Europeanization. The framework of the negative perceptions of the EU in the discourse of politicians and state officials is constituted by implicit and explicit constructs of unstable, fickle and irresponsible EU who threatens, orders, and humiliates. Extreme anti-European opinions towards Europe are expressed through the open hate speech and the banalization and spectacularization of the topic. Analysis of conceptual metaphors in the sample showed that the previously observed patterns of conceptualization of the European Union as a model to follow has not changed and that they are still present in the media discourse of Serbian media.
Keywords: Europeanization; media representations; Media Discourse; media; Serbia